10′(Z),13′(E)-Heptadecadienylhydroquinone Inhibits Swarming and Virulence Factors and Increases Polymyxin B Susceptibility in Proteus mirabilis - Liu, Ming-Che; Lin, Shwu-Bin; Chien, Hsiung-Fei; Wang, Won-Bo; Yuan, Yu-Han; Hsueh, Po-Ren; Liaw, Shwu-Jen (PloS one, 2012)
In this study, we demonstrated that 10'(Z), 13'(E)-heptadecadienylhydroquinone (HQ17-2), isolated from the lacquer tree, could decrease swarming motility and hemolysin activity but increase polymyxin B (PB) susceptibilityof Proteus mirabilis which is intrinsically highly-resistant to PB. The increased PB susceptibility induced by HQ17-2 was also observed in clinical isolates and biofilm-grown cells. HQ17-2 could inhibit swarming in the wild-type and rppA mutant but not in the rcsB mutant, indicating that HQ17-2 inhibits swarming through the RcsB-dependent pathway, a two-component signaling pathway negatively regulating swarming and virulence factor expression. The inhibition of hemolysin activity by HQ17-2 is also mediated through the RcsB-dependent pathway, because HQ17-2 could not inhibit hemolysin activity in the rcsB mutant. Moreover, the finding that HQ17-2 inhibits the expression of flhDC gene in the wild-type and rcsB-complemented strain but not in the rcsB mutant supports the notion. By contrast, HQ17-2 could increase PB susceptibility in the wild-type and rcsB mutant but not in the rppA mutant, indicating that HQ17-2 increases PB susceptibility through the RppA-dependent pathway, a signaling pathway positively regulating PB resistance. In addition, HQ17-2 could inhibit the promoter activities of rppA and pmrI, a gene positively regulated by RppA and involved in PB resistance, in the wild-type but not in the rppA mutant. The inhibition of rppA and pmrI expression caused lipopolysaccharide purified from HQ17-2-treated cells to have higher affinity for PB. Altogether, this study uncovers new biological effects of HQ17-2 and provides evidence for the potential of HQ17-2 in clinical applications.